Prospective Observational Study to Assess Quality of Life before and after Introduction of Probiotic Nutraceuticals and Probiotic Food (Curd) in Subjects with Depression: A Comparative Analysis - Sanmith Tarikere Doddamane; Abhay Paliwal; Koustubh Bagul; Nishant Patel (Indian Journal of Private Psychiatry)
Background: Depression poses a pervasive challenge to individuals’ well-being, prompting the exploration of alternative therapies due to the limited efficacy of traditional treatments. Recent research has investigated the potential therapeutic role of probiotics, including probiotic nutraceuticals and the probiotic food curd, in addressing mental health concerns. Materials and methods: This 28-day prospective observational study aimed to assess the impact of probiotic interventions on the quality of life in individuals aged 18–60 diagnosed with mild to moderate depression according to ICD-10 criteria. Ninety participants were divided into three groups: One group received probiotic nutraceuticals along with escitalopram, another group received probiotic food (curd) along with escitalopram, and the third group was treated with escitalopram alone. The World Health Organization (WHO) quality of life (WHOQOL-BREF) scale measured participants’ quality of life at the study’s initiation and conclusion. Data analysis utilized comparative and statistical methods to evaluate the intervention’s impact. Results: Significant improvements in quality of life were observed in individuals with depression after 28 days of treatment. The probiotic group exhibited the most substantial increase in WHOQOL-BREF scores, rising significantly from an initial mean of 34.73 ± 1.55 on day 0 to 46.72 ± 2.47 on day 28 (p < 0.001). In comparison, the escitalopram group showed an increase from 34.58 ± 1.82 to 42.37 ± 2.54 (p < 0.001), and the curd group improved from 35.28 ± 1.35 to 44.43 ± 2.36 (p < 0.001). Conclusion: This study highlights the potential of probiotics as valuable adjuncts to traditional treatments for major depressive disorder (MDD). The findings emphasize holistic approaches to mental health management, opening new avenues for improving the lives of individuals grappling with depression. Despite limitations, this research encourages further exploration and applications of probiotics in mental health care.